PENERAPAN METODE STRUKTURAL ANALISIS SINTESIS (SAS) UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN PADA SISWA KELAS I SD NEGERI 184 PEKANBARU - ', Hasraininur; ', Hamizi; ', Erlisnawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : Formular of problem of research is: Can application SAS method inprove beginning ability of reading to the first class of public elementary school students 184 Pekanbaru? Purpose of research to improve beginning ability of reading the first class public elementary school student 184 Pekanbaru using SAS method. Hypothensis action is if application SAS method implied so that can improve beginning ability of reading the first class public elementary school student 184 Pekanbaru in school year 2014 / 2015 to student total as many as 30 persons. The research is implied in two cycle, the first cycle of students complete 21 persons and incomplete 10 persons and the second cycle of students complete 27 persons and incomplete 4 persons. Teacher’s observation result of research show there is activity improvement in the first cycle meeting 67%, the second cycle meeting 75%. Student’s activity result show there are students activity improvement to the first cycle meeting 53,12%. The second cycle meeting 59,37%, the second cycle of the first meeting 78,12%. The second cycle of the second meeting 90,62%. Result ability of reading in the first learning SAS method to class complitftion beginning ability of the students reading only 32,25% and incomplete 67,74% after using SAS method learning classical complitation of beginning students ability reading in the first daily test (UH1) improve become 67,74% and incomplete 32,25% then in the second daily test (UH2) improve become 87.09% and incomplete12,90% thus with hypothensis action sound if application SAS method is implied so can improve beginning the first students ability of reading public elementary school students 184 Pekanbaru, can be accepted.Keyword : Beginning ability of reading SAS method.